Containment Bag Use Among Women Who Undergo Hysterectomy With Laparoscopic Power Morcellation. Issue 3 (3rd September 2022) - Wright, Jason D.; Chen, Ling; Melamed, Alexander; Clair, Caryn M. St.; Hou, June Y.; Khoury-Collado, Fady; Gockley, Allison; Accordino, Melissa; Hershman, Dawn L.; Xu, Xiao
Abstract : Containment bag use for laparoscopic hysterectomy increased after the U.S. Food and Drug Administration's 2014 guidance; however, most procedures employing laparoscopic power morcellators are still performed without a containment bag. Abstract : OBJECTIVE: To estimate trends in use of laparoscopic power morcellators in women undergoing minimally invasive hysterectomy and to examine use of containment systems in these patients in relation to safety guidance from the U.S. Food and Drug Administration (FDA). METHODS: We examined data that were recorded in the Premier Healthcare Database from patients who underwent laparoscopic supracervical hysterectomy from 2010 to 2018. Patients were stratified based on use of laparoscopic power morcellators. The cohort was further stratified as either pre–FDA guidance (2010 quarter 1–2014 quarter 1) or post–FDA guidance (2014 quarter 2–2018 quarter 2). Interrupted time series analyses were performed to determine the effect of FDA guidance on the use of laparoscopic power morcellators and containment bags. RESULTS: Among 67, 115 patients, laparoscopic power morcellator use decreased from 66.7% in 2013 quarter 4 to 13.3% by 2018 quarter 2. The likelihood of laparoscopic power morcellator use decreased by 9.5% for each quarter elapsed in the post–FDA warning period (risk ratio [RR] 0.91, 95% CI 0.90–0.91). Containment bag use rose from 5.2% in 2013 quarter 4 to 15.2% by 2018 quarter 2. The likelihood of containment bag use increased by 3% for each quarter elapsed in the post–FDA warning period (RR 1.03, 95% CI 1.02–1.05). Among women who had laparoscopic power morcellator use, uterine cancers or sarcomas were identified in 54 (0.17%) before the FDA guidance compared with seven (0.12%) after the guidance ( P =.45). Containment bags were used in 11.1% of women with uterine cancers or sarcomas before the FDA guidance compared with 14.3% after the guidance ( P =.12). The perioperative complication rate was 3.3% among women who had laparoscopic power morcellator use without a containment bag compared with 4.5% ( P =.001) in those with a containment bag (aRR 1.35, 95% CI 1.12–1.64). CONCLUSION: Use of laparoscopic power morcellators has decreased over time. Containment bag use increased after the FDA's 2014 guidance; however, most procedures employing laparoscopic power morcellators are still performed without a containment bag.